The Negative Predictive Ability of Immature Neutrophils for Bacteremia in Children With Community-Acquired Infections - Pimentel, Alexandre M.; Vilas-Boas, Caroline C.; Vilar, Ticiana S.; Nascimento-Carvalho, Cristiana M. (Frontiers in Pediatrics, 2020)
Background: Bacteremia is a serious condition. We aimed to assess the role of immature neutrophils in peripheral blood smears for prediction of bacteremia in children. Methods: In this cross-sectional study conducted in Salvador, Brazil, blood cultures collected from patients aged ≤18 years were identified. White Blood Cell count (WBC) was performed upon admission. Medical charts were reviewed and cases from the community were included. Results: Out of 833 potentially eligible patients, 263 (31.6%) were excluded. Therefore, the study group comprised 570 patients being blood collected for culture upon admission from all of them and WBC performed upon admission from 566. The median age was 2 years (IQR: 9.4 mo−5 y) and 300 (52.6%) were male. Acute respiratory infection was the most frequent diagnosis (n = 388; 68.1%), being 250 (43.9%) lower (LRTI) and 138 (24.2%) upper respiratory tract infections. Blood culture was positive in 9 (1.6%; 95% CI: 0.8–2.9%) cases, out of which 7 (2.8%) had LRTI. Streptococcus pneumoniae (n = 3), Haemophilus (n = 2), Neisseria meningitidis, viridans streptococci, Streptococcus agalactiae, and Acinetobacter baumanii (n = 1 each) were isolated. The total WBC/mm3 did not differ when children with positive or negative blood culture were compared (12,100 [IQR: 6,950–15,250] vs. 11,000 [IQR: 7,900–14,900]; P = 0.9). However, presence of any immature neutrophil was significantly more frequent among patients with bacteremia in comparison with patients without bacteremia (100% [9/9] vs. 40% [223/557]; P < 0.001). The absolute number of immature neutrophils was significantly lower among children without bacteremia (0 [IQR: 0–259] vs. 325 [IQR: 275–1,106]; P < 0.001). Overall, the area under the ROC curve of the number of immature neutrophils in regard to bacteremia was 0.82 (95% CI: 0.76–0.88; P = 0.001). Among 413 patients with absolute number of immature neutrophils <242/mm3, none had bacteremia; among 153 patients with absolute number of immature neutrophils ≥242/mm3, 9 (5.9%) had bacteremia. Absolute number of immature neutrophils ≥242/mm3 showed: sensitivity 100% (95% CI: 71.7–100%), specificity 74.1% (95% CI: 70.4–77.7%), negative predictive value 100% (95% CI: 99.3–100.0%), and positive predictive value 5.9% (95% CI: 2.9–10.5%). When only children with LRTI were analyzed, the results were similar. Conclusion: The absolute number of immature neutrophils in peripheral blood smear is a potential tool to rule out bacteremia among children with community-acquired infections.